PENGGUNAAN MODEL PROBLEM BASED LEARNING DENGAN KOLABORASI GAMES UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS, KEKTIFAN DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH PENGANTAR BISNIS - Roza, Silvia (Ensiklopedia of Journal, 2024)
This research aims to determine the use of the problem based learning model with collaborative games to improve students' critical thinking skills, effectiveness and learning outcomes in introductory business courses. This type of research is classroom action research. The population in this study was 16 economic education study program students taking introductory business courses. By using a saturated sampling technique, the sample for this research is 16 students from the class of 2023. The analysis techniques used in this research are descriptive analysis The results of this research show that using the problem based learning model with the help of games has improved students' critical thinking skills. From the beginning students just sat listening to their friends discussing and only gave a little feedback, when it was replaced with the problem based learning model and collaborated with games students were more willing to express his opinion. Apart from critical thinking, students' activity has also increased, this can be seen from the way they express ideas, they try to compete to find out and get answers to problems and argue with each other. From the other side, student learning outcomes have also increased from pre-cycle with an average of 67.81 to 75.84 in cycle I and 81.30 in cycle II. So it can be concluded that the problem based learning model can improve critical thinking skills, student creativity and student learning outcomes.Keywords: Problem based learning model, critical thinking skills, activeness and learning outcomes, students